Light-Responsive Micelles Loaded With Doxorubicin for Osteosarcoma Suppression - Chen, Jiayi; Qian, Chenhong; Ren, Peng; Yu, Han; Kong, Xiangjia; Huang, Chenglong; Luo, Huanhuan; Chen, Gang (Frontiers in Pharmacology, 2021)
The enhancement of tumor targeting and cellular uptake of drugs are significant factors in maximizing anticancer therapy and minimizing the side effects of chemotherapeutic drugs. A key challenge remains to explore stimulus-responsive polymeric nanoparticles to achieve efficient drug delivery. In this study, doxorubicin conjugated polymer (Poly-Dox) with light-responsiveness was synthesized, which can self-assemble to form polymeric micelles (Poly-Dox-M) in water. As an inert structure, the polyethylene glycol (PEG) can shield the adsorption of protein and avoid becoming a protein crown in blood, improving the tumor targeting of drugs and reducing the cardiotoxicity of doxorubicin (Dox). Besides, after ultraviolet irradiation, the amide bond connecting Dox with PEG can be broken, which induced the responsive detachment of PEG and enhanced cellular uptake of Dox. Notably, the results of immunohistochemistry in vivo showed that Poly-Dox-M had no significant damage to normal organs. Meanwhile, they showed efficient tumor-suppressive effects. This nano-delivery system with the light-responsive feature might hold great promises for the targeted therapy for osteosarcoma.